VEGFA and tumour angiogenesis. (19th January 2013) - Claesson‐Welsh, L.; Welsh, M.
Abstract In this review we summarize the current understanding of signal transduction downstream of vascular endothelial growth factor A (VEGFA) and its receptor VEGFR2, and the relationship between these signal transduction pathways and the hallmark responses of VEGFA, angiogenesis and vascular permeability. These physiological responses involve a number of effectors, including extracellular signal‐regulated kinases (ERKs), Src, phosphoinositide 3 kinase (PI3K)/Akt, focal adhesion kinase (FAK), Rho family GTPases, endothelial NO and p38 mitogen‐activated protein kinase (MAPK). Several of these factors are involved in the regulation of both angiogenesis and vascular permeability. Tumour angiogenesis primarily relies on VEGFA‐driven responses, which to a large extent result in a dysfunctional vasculature. The reason for this remains unclear, although it appears that certain aspects of the VEGFA‐stimulated angiogenic milieu (high level of microvascular density and permeability) promote tumour expansion. The high degree of redundancy and complexity of VEGFA‐driven tumour angiogenesis may explain why tumours commonly develop resistance to anti‐angiogenic therapy targeting VEGFA signal transduction.